1992
DOI: 10.1016/0014-5793(92)80053-j
|View full text |Cite
|
Sign up to set email alerts
|

17O NMR and FT‐IR study of the ionization state of peptides in aprotic solvents Application to Leu‐enkephalin

Abstract: The ionization state of Leu-enkephalin in DIMSO and MeCNlDMSO (4/l) solution was studied by the combined use of "0 NMR and FT-IR spectroscopy. After lyophilization of an aqueous solution at nearly neutral pH, Leu-enksphalin essentially exists in the uncharged state in MeCN/DMSO (4/l) solution. In pure DMSO, only 40% of the Leu-enkephalin molecules are in the zwittcricnic state under Ihe same conditions. FT-IR; Ionization state of peptide; Leu-enkephalin: "0 NMR 1, INTRODUCTION 2. MATERIALS AND METHODSMany conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…1600 cm Ϫ1 . As reported earlier, 35 the protonation equilibrium in TFE is not shifted completely towards the zwitterionic form: NH 2 -peptide-COOH ϩ NH 3peptide-COO Ϫ ϩ NH 3 -peptide-COOH. In the case of trifluoroacetate salts 6, 7 and 11, the IR spectra of which are dominated by the strong ν as band of CF 3 COO Ϫ at 1675 cm Ϫ1 , a positively charged species with a free COOH function also appears.…”
Section: Ftir Studiessupporting
confidence: 75%
“…1600 cm Ϫ1 . As reported earlier, 35 the protonation equilibrium in TFE is not shifted completely towards the zwitterionic form: NH 2 -peptide-COOH ϩ NH 3peptide-COO Ϫ ϩ NH 3 -peptide-COOH. In the case of trifluoroacetate salts 6, 7 and 11, the IR spectra of which are dominated by the strong ν as band of CF 3 COO Ϫ at 1675 cm Ϫ1 , a positively charged species with a free COOH function also appears.…”
Section: Ftir Studiessupporting
confidence: 75%
“…It is worth mentioning here that originally we tried to dissolve the molecule in CCl 4 solvent, but due to solubility, DMSO-d 6 was then used. Moreover, an MD simulation 52 of [Leu]enkephalin, NMR and FTIR study of the solvent effect 53 and a DFT study of this molecule 54 suggested the presence of both zwitterionic and neutral species in DMSO. Taking these results into consideration, the discrepancy can also be attributed to the fact that our calculations are based on the presence of only the neutral species.…”
Section: Resultsmentioning
confidence: 99%
“…Asp1 related NOESY cross‐peaks are limited for both peptides, and this is the major drawback in ambiguous conformational investigation of the N‐terminus. Possibly, dimethylsulfoxide accounts for the loss of backbone amide proton of Asp1 [63] resulting in considerable loss of intraresidue scalar or inter‐residue NOE contacts.…”
Section: Discussionmentioning
confidence: 99%